Intestinal epithelial cells contribute to the enhanced generation of platelet activating factor in ulcerative colitis. Issue 5 (May 1993) - Ferraris, L; Karmeli, F; Eliakim, R; Klein, J; Fiocchi, C; Rachmilewitz, D
Abstract : Generation of platelet activating factor by intestinal mucosal epithelial cells and lamina propria mononuclear cells was evaluated to elucidate the possible role of this mediator in the pathogenesis of inflammatory bowel disease. Epithelial and lamina propria mononuclear cells were isolated from surgical specimens from control, Crohn's disease, and ulcerative colitis patients. Platelet activating factor was extracted from highly purified cell preparations with 80% ethanol after stimulation with and without 0.2 uM calcium ionophore A23187 and was measured by platelet aggregation assay. Both cell types generated platelet activating factor activity and this was generally comparable for epithelial and lamina propria cells. Basal and stimulated platelet activating factor activity of epithelial and lamina propria cells from ulcerative colitis but not Crohn's disease patients was appreciably higher than that of control. Stimulation with calcium ionophore increased appreciably platelet activating factor activity in lamina propria cells from all groups. In contrast, only epithelial cells from ulcerative colitis showed an appreciable increase after calcium ionophore induction. These results suggest that epithelial cells are important contributors to intestinal platelet activating factor generation under normal and inflammatory conditions and that epithelial cells actively play a part in the pathogenesis of ulcerative colitis.